Floristic and Phenological Analysis of Ground Vegetation Growth under Eucalyptus hybrid and Dalbergia sissoo Plantation - bhatt, bhavtosh (Indian Forester, 2020)
The present study deals with phytosociological and phenology of ground vegetation in Eucalyptus hybrid and Dalbergia sissoo plantation in Haridwar forest division. The total number of plant species were recorded as 39, 35, 28 in E. hybrid and 29, 25, 23 in D. sissoo during rainy, winter and summer season respectively. Chrysopogon fulvus was dominating the community grown under E. hybrid plantation by having maximum value of IVI and co-dominating by Arundinella nepalensis. However Parthenium hysterophorus was dominated by Cynodon dactylon and Oxalis corniculata. the phenological study of ground vegetation revealed that majority of annuals flowers fruit and produced their seeds in rainy season while fruiting and seed maturation in a number of perennial are activated during winter.